Scriptural legitimation and the mobilisation of support for religious violence: experimental evidence across three religions and seven countries - Ruud Koopmans; Eylem Kanol; Dietlind Stolle (Journal of Ethnic and Migration Studies, 2021)
In their attempts to mobilise supporters and justify their actions, violent religious extremists often refer to parts of scripture that legitimize violence against supposed enemies of the faith. Accounts of religious extremism are divided on whether such references to scripture have genuine motivating and mobilising power. We investigate whether references to legitimations of violence in religious scripture can raise support for religious violence by implementing a survey experiment among 8,000 Christian, Muslim and Jewish believers in seven countries across Europe, North America, the Middle East and Africa. We find that priming individuals with isomorphic pro-violence quotes from Bible, Torah or Quran raises attitudinal support for religious violence significantly. Effect sizes are particularly large among those with a fundamentalist conception of their religion. Our results show that religious scripture can be effectively used to mobilise support for violence. The findings thus mark a counterpoint to theoretical arguments that question the causal role of religion and have important implications for de-radicalization policies.
doi:10.7802/2104
Keywords: 300; religious fundamentalism; violence; Islam; Christianity; Judaism